Biosimilar filgrastim vs filgrastim: a multicenter nationwide observational bioequivalence study in patients with chemotherapy-induced neutropenia - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2018)
Background: We studied the comparative effectiveness of biosimilar filgrastim vs original filgrastim in patients with chemotherapy-induced neutropenia. Patients and methods: This multicenter, observational study was conducted at 14 centers. The study included 337 patients experiencing neutropenia under chemotherapy. Patients were given either filgrastim 30 MIU or 48 MIU (Neupogen (R)) or biosimilar filgrastim 30 MIU (Leucostim (R)). Data regarding age, chemotherapeutic agents used, number of chemotherapy courses, previous diagnosis of neutropenia, neutrophil count of patients after treatment, medications used for the treatment of neutropenia, and duration of neutropenia were collected. Time to absolute neutrophil count (ANC) recovery was the primary efficacy measure. Results: Ambulatory and hospitalized patients comprised 11.3% and 45.1% of the enrolled patients, respectively, and a previous diagnosis of neutropenia was reported in 49.3% of the patients, as well. Neutropenia occurred in 13.7% (n=41), 45.5% (n=136), 27.4% (n=82), 11.4% (n=34), and 2.0% (n=6) of the patients during the first, second, third, fourth, and fifth cycles of chemotherapy, respectively. While the mean neutrophil count was 0.53 +/- 0.48 before treatment, a significant increase to 2.44 +/- 0.66 was observed after treatment (p=0.0001). While 90.3% of patients had a neutrophil count,1.49 before treatment, all patients had a neutrophil count >= 1.50 after treatment. Neutropenia resolved within <= 4 days of filgrastim therapy in 60.1%, 56.7%, and 52.6% of the patients receiving biosimilar filgrastim 30 MIU, original filgrastim 30 MIU, and original filgrastim 48 MIU, respectively. However, there was no significant difference between the three arms (p=0.468). Similarly, time to ANC recovery was comparable between the treatment arms (p=0.332). Conclusion: The results indicate that original filgrastim and biosimilar filgrastim have comparable efficacy in treating neutropenia. Biosimilar filgrastim provides a valuable alternative; however, there is need for further studies comparing the two products in different patient subpopulations.
Keywords: chemotherapy; febrile neutropenia; neutrophil; ANC recovery; supportive care; myelosuppressive; COLONY-STIMULATING FACTOR; NON-HODGKINS-LYMPHOMA; FEBRILE NEUTROPENIA; G-CSF; RECEIVING CHEMOTHERAPY; CANCER-CHEMOTHERAPY; BREAST-CANCER; LUNG-CANCER; RISK; CHOP